ERIA CONTRIBUTION TO DEVELOPMENT OF ASEAN INFRASTRUCTURE THROUGH COMPREHENSIVE ASIAN DEVELOPMENT PLAN (CADP) - Nanda Sucitra Putri; Denise Ann Kamano (Journal of International Relations, 2022)
This study aims to analyse ERIA’s contribution as an international organization and economic research institute, in its’ involvement to support the ASEAN infrastructure development through Comprehensive Asian Development Plan (CADP). CADP was first submitted to the East Asia Summit in 2010, to implant and to pursue both deepening economic integration and narrowing development gaps by illustrating a grand spatial design of both economic infrastructure and industrial placement in ASEAN and East Asia. It also explained further about the digital development which has happened in East Asia and reviewed every five years. Authors used a descriptive qualitative research methodology towards the contribution made by ERIA in infrastructure building of ASEAN. From our findings, we can conclude that CADP, in line with the goals set in ASEAN Community Pillars, made development and infrastructure growth in ASEAN increased significantly, and will continue to do so from the phases set in their goals.Keywords: ASEAN, infrastructure, development, ICT, CADP, Community Pillars, economy.